2001
DOI: 10.1103/physrevlett.86.4267
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Continuous Variable Einstein-Podolsky-Rosen Entanglement via the Kerr Nonlinearity in an Optical Fiber

Abstract: We report on the generation of a continuous variable Einstein-Podolsky-Rosen (EPR) entanglement using an optical fibre interferometer. The Kerr nonlinearity in the fibre is exploited for the generation of two independent squeezed beams. These interfere at a beam splitter and EPR entanglement is obtained between the output beams. The correlation of the amplitude (phase) quadratures are measured to be 4.0 ± 0.2 (4.0 ± 0.4) dB below the quantum noise limit. The sum criterion for these squeezing variances 0.80 ± 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
168
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(171 citation statements)
references
References 20 publications
2
168
1
Order By: Relevance
“…Kerr interaction has been suggested to realize quantum nondemolition measurements, to enhance quantum estimation performances in quantum optics and to generate quantum superpositions [111,112] as well as squeezing [113] and entanglement [58,59]. A known example of Kerr medium is provided by optical fibers where, however, nonlinearities are small and accompanied by other unwanted effects.…”
Section: Kerr Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kerr interaction has been suggested to realize quantum nondemolition measurements, to enhance quantum estimation performances in quantum optics and to generate quantum superpositions [111,112] as well as squeezing [113] and entanglement [58,59]. A known example of Kerr medium is provided by optical fibers where, however, nonlinearities are small and accompanied by other unwanted effects.…”
Section: Kerr Interactionmentioning
confidence: 99%
“…For γ ≈ 10 −2 the maximum nG achievable at fixed energy is quite rapidly achieved, while for more realistic values of the Kerr coupling nG is obtained only for large values of the average number of photons. In the experiments proposed to obtain entanglement via Kerr interaction [58,59], pulses with an average number up to 10 8 photons are needed to compensate the small nonlinearities of standard glass fibers. Therefore, in these regimes, the generation of entanglement is always accompanied by a large degree of nG.…”
Section: Kerr Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, RIS can also occur between orthogonal polarization components of a single light beam. In such case, the field is said to be polarization squeezed [8,9] and the noise reduction is described in terms of squeezing of the fluctuations of one of the Stokes operators:Here a x , a y are the field destruction operators for the orthogonal linear polarizations x and y. Polarization squeezing has been produced via propagation in optical fibers [10,11], through the combination on a polarizing beam splitter of two quadrature squeezed light beams [12] and through the interaction of linearly polarized light with cold atoms inside an optical cavity [9,13].It has been recently demonstrated that the single passage of a linearly polarized pump beam through a few-cmlong atomic vapor cell results in squeezing of the polarization orthogonal to that of the pump (vacuum squeezing) [14][15][16][17] as a consequence of the nonlinear optics mechanism known as polarization self-rotation (PSR) [18][19][20]. Vacuum squeezing via PSR has been observed for the D1 [15][16][17] and D2 [14] transitions using 87 Rb vapor.…”
mentioning
confidence: 99%
“…In fact, there are strong similarities between a quantum regime SQUID ring and a device frequently employed in quantum optics-the nonlinear optical coupler-this being formed from two or more linearly coupled waveguides where at least one is composed of an optically nonlinear medium. [41][42][43][44][45] However, there are two important differences between optical couplers and the SQUID ring: ͑i͒ optical nonlinear interactions usually have a nonresonant character and ͑ii͒ optical nonlinear couplers are difficult to make because of the strict phase and frequency matching conditions that must be obeyed by all involved processes simultaneously. Hence, it may well be that SQUID ring coupled devices, such as those presented here, could lead to a feasible way of realizing ͑or at least simulating͒ nonlinears optical couplers.…”
Section: Discussionmentioning
confidence: 99%